Conjunctival Epithelial Inclusion Cyst - Shivraj Tagare; Josephine S Christy (Delhi Journal of Ophthalmology)
We present a case of conjunctival inclusion cyst which was misdiagnosed as a lid swelling at first instance. The swelling moved upwards on lid closure mimicking a mobile chalazion. On lifting up the lid, the transilluminant conjunctival cyst was revealed at scleral tunnel. Histopathological examination confirmed the diagnosis of inclusion cyst. This case depicts the importance of lifting the lids and thorough examination in all cases of lid swelling because of potential underlying pathologies arising from inner coats of eye ball that can closely mimic it.